Interactive Performance-Oriented Mobility Assessment (iPOMA) - Jorge Ruiz; Guillermo Morel; Michael Smith; Osvaldo Rodriguez; Aaron McEntire; Saleh Hernandez; Axel Juan; Maria van Zuilen; Michael Mintzer (Association of American Medical Colleges, 2006)
Abstract The Performance Oriented Mobility Assessment (POMA), which is based on the fall risk assessment tool developed by M. Tinetti, has been used to assess fall risk in a wide variety of outpatient, acute, home, and long-term care settings. The instrument has been modified over the years in order to measure usual function rather than standard function, and the maneuvers included are based on the position changes and gait activities used during daily activity. Hence this particular instrument includes some maneuvers designed to measure the individual's function in the individual's most natural setting, his or her home, as opposed to the laboratory or the clinical setting. The inter-rater reliability for this instrument has been determined at around 83%. In a group of community dwelling elderly, the sensitivity and specificity was 70% and 52% respectively. This particular version has a greater number of maneuvers with a wider spectrum of difficulty in order to increase the sensitivity of the instrument. The maximum number of points that can be achieved is 35. The lower the score, the higher the fall risk, but there are no predetermined cut-off points. The score can be used as a baseline prior to implementing a therapeutic intervention for a particular individual. The maneuvers measured are likely to improve with a therapeutic intervention. The individual can be tested again at the end of the intervention to assess response to therapy. The POMA can be administered in 10-15 minutes. Complete data was gathered from 95 second-year medical students. Self-efficacy ratings (on a 5-point scale) increased from 3.4 before the tutorial to 4.2 after the online tutorial (t = 6.86, p < .001). Self-efficacy ratings after the tutorial were significantly correlated with the online quiz score (r = .391, p < .001), indicating genuine increases in students' capabilities. Students rated their overall experiences as "good," and the tutorial as "easy" to use.